Tuberculosis in Vaccinated versus Unvaccinated Children with BCG Vaccine in Niamey: Epidemiological, Diagnostic and Outcome Aspects - Samaila Aboubacar; Soumana Alido; Kamaye Moumouni; Mamoudou Abdou Djafar; Garba Moumouni; Gagara Issoufou Madougou Assiatou; Moussa Ounteini Abasse; Marou Soumana Boubacar; Ide Amadou Habiba; Nanaito Nafissatou; Georges Thomas Ibrahim (European Scientific Journal, ESJ, 2022)
Introduction: Tuberculosis remains a public health problem worldwide. The BCG vaccination is one of the response means. The objective of this work was to study the impact of BCG vaccination on morbidity and mortality related to childhood tuberculosis in Niamey. Patients and methods: It was a multicenter prospective and comparative study from January to September 2017 in two-referral hospital centers of Niamey and the National Anti-Tuberculosis Center. The study population consisted exclusively of children aged 0 to 15 years old suffering from tuberculosis. Epidemiological, diagnostic, and evolving aspects in vaccinated and unvaccinated children were studied. Statistical tests used were Pearson's Chi² and Fisher's exact test (p <0.05). Results: Ninety-one children were studied. The BCG vaccination rate was 60.4%. The mean age of children was 6 years 11 months [3 months-15 years]. Children under 2 years of age were less affected (11%) in vaccinated children than in unvaccinated children (3.2%). No association was found between the duration of tuberculosis signs (p = 0.37), expression of tuberculin skin test (p = 0.43), and the children's BCG vaccination status. On the other hand, there was a significant link between vaccination status and the occurrence of complications (p = 0.014), and death risk (p = 0.003). Conclusion: This study shows that children’s BCG vaccination status correlates with some aspects of tuberculosis. Unvaccinated children have a significantly higher risk of complications and death from TB.